2012
DOI: 10.2319/052911-356.1
|View full text |Cite
|
Sign up to set email alerts
|

Auriculo-condylar syndrome

Abstract: The auriculo-condylar syndrome is caused by abnormalities of the first and second pharyngeal arches during embryonic development. Its inheritance follows the autosomal dominant pattern. Both familial and individual cases are reported in the literature. The syndrome is characterized by wide phenotypic variation, with affected individuals expressing clinical signs of variable severity due to variable expressivity of the responsible genes. Clinical signs of the syndrome include auricular malformation, hypoplasia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…However, to date, only a limited number of sporadic ARCND cases have been reported. Ozturk et al [ 20 ], Papagrigorakis et al [ 21 ], Greig et al [ 10 ], and Yang et al [ 11 ] reported the use of a porous polyethylene prosthesis, DO, TMJ reconstruction, mandibular iliac bone transplantation, and Le Fort type I osteotomy to treat patients with ARCND. However, the application of preoperative orthodontics, DO, maxillary Le Fort I osteotomy, BSSRO, horizontal osteotomy, and genioplasty to treat adult patients with ARCND simultaneously has not yet been reported.…”
Section: Discussionmentioning
confidence: 99%
“…However, to date, only a limited number of sporadic ARCND cases have been reported. Ozturk et al [ 20 ], Papagrigorakis et al [ 21 ], Greig et al [ 10 ], and Yang et al [ 11 ] reported the use of a porous polyethylene prosthesis, DO, TMJ reconstruction, mandibular iliac bone transplantation, and Le Fort type I osteotomy to treat patients with ARCND. However, the application of preoperative orthodontics, DO, maxillary Le Fort I osteotomy, BSSRO, horizontal osteotomy, and genioplasty to treat adult patients with ARCND simultaneously has not yet been reported.…”
Section: Discussionmentioning
confidence: 99%
“…The dominant characteristic features of ACS include micrognathia, small mandibular condyle, and question-mark ear. Severe small mandible ACS patients usually need bilateral mandibular ramus enlargement, which could be obtained from distraction osteogenesis or orthognathic surgery, which is time-consuming and expensive [3]. On the contrary, excessive bone formation lays behind mandibular prognathism which is a maxillofacial disorder characterized by an abnormal forward projection of the lower jaw [4].…”
Section: Introductionmentioning
confidence: 99%
“…There is wide clinical variability, including cases with isolated ear anomalies. Treatment is mainly corrective through surgical intervention for mandibular ramus lengthening using distraction osteogenesis and accompanied by orthodontic treatments and speech therapy 3. Understanding the aetiology of this disorder and elucidating genetic causes improve counselling and may lead to the development of preventive or therapeutic strategies, besides deepening our knowledge of craniofacial development.…”
Section: Introductionmentioning
confidence: 99%